Evolution of a rare ECG pattern in an aggressive case of neonatal tuberous sclerosis complex. (2018) - Iezzi, Federica; Quarti, Andrea; Capestro, Alessandro; Surace, Francesca Chiara; Pozzi, Marco
Highlights: Cardiac rhabdomyomas may alter intracardiac electrical conduction. Rhabdomyoma arrhythmias are caused by isolated atrial depolarization disturbances. Destruction of conduction system has been described in diffuse rhabdomyomatosis. Abstract: Introduction: Rhabdomyomas are the most frequent cardiac tumors in children. Furthermore, they are often associated to tuberous sclerosis complex, an autosomal dominant neurocutaneous disorder characterized by tumor-like malformations that involve many organ systems. Presentation of the case: We describe a rare ECG pattern in a severe case of neonatal tuberous sclerosis complex. Discussion: In the presence of significant rhabdomyomatosis related to tuberous sclerosis, multiple clusters of rhabdomyoma-like cells can infiltrate the myocardium, with increased fibrosis areas. Conclusion: Considering the fact that rhabdomyomas often show spontaneous regression, close follow-up is sufficient in hemodynamically stable cases. Destruction of the conduction system, with arrhythmias as consequence, can be the presenting feature of diffuse rhabdomyomatosis.